The cost‐effectiveness of HIV pre‐exposure prophylaxis in men who have sex with men and transgender women at high risk of HIV infection in Brazil. Issue 3 (30th March 2018) - Luz, Paula M; Osher, Benjamin; Grinsztejn, Beatriz; Maclean, Rachel L; Losina, Elena; Stern, Madeline E; Struchiner, Claudio J; Parker, Robert A; Freedberg, Kenneth A; Mesquita, Fabio; Walensky, Rochelle P; Veloso, Valdilea G; et al.
Abstract: Introduction: Men who have sex with men (MSM) and transgender women (TGW) in Brazil experience high rates of HIV infection. We examined the clinical and economic outcomes of implementing a pre‐exposure prophylaxis (PrEP) programme in these populations. Methods: We used the Cost‐Effectiveness of Preventing AIDS Complications (CEPAC)‐International model of HIV prevention and treatment to evaluate two strategies: the current standard of care (SOC) in Brazil, including universal ART access ( No PrEP strategy); and the current SOC plus daily tenofovir/emtracitabine PrEP ( PrEP strategy) until age 50. Mean age (31 years, SD 8.4 years), age‐stratified annual HIV incidence (age ≤ 40 years: 4.3/100 PY; age > 40 years: 1.0/100 PY), PrEP effectiveness (43% HIV incidence reduction) and PrEP drug costs (23/month) were from Brazil‐based sources. The analysis focused on direct medical costs of HIV care. We measured the comparative value of PrEP in 2015 United States dollars (USD) per year of life saved (YLS). Willingness‐to‐pay threshold was based on Brazil's annual per capita gross domestic product (GDP; 2015: 8540 USD). Results: Lifetime HIV infection risk among high‐risk MSM and TGW was 50.5% with No PrEP and decreased to 40.1% with PrEP . PrEP increased per‐person undiscounted (discounted) life expectancy from 36.8 (20.7) years to 41.0 (22.4) years and lifetime discounted HIV‐related medical costs from 4100 to 8420, which led to an incremental cost‐effectiveness ratio (ICER) of 2530/YLS. PrEP remained cost‐effective (<1x GDP) under plausible variation in key parameters, including PrEP effectiveness and cost, initial cohort age and HIV testing frequency on/off PrEP. Conclusion: Daily tenofovir/emtracitabine PrEP among MSM and TGW at high risk of HIV infection in Brazil would increase life expectancy and be highly cost‐effective.